Partnership as a factor in the development of corporate volunteering - Helen Chuiko (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2015)
The article reveals the theoretical and applied foundations of the implementation of corporate volunteering in the practice of charity. Describes the results of a study aimed at investigating the characteristics of building partnerships between business companies and non-governmental or- ganizations in the practice of corporate volunteering.